A review of the genus Aulacogenia Stal (Heteroptera: Reduviidae: Stenopodainae) from China - Zhao, Ping; Cai, Wanzhi; Tomokuni, Masaaki (Zootaxa, 2005)
The species of the genus Aulacogenia Stål from China are reviewed. Five species are recognized, described or redescribed, illustrated, and keyed. A. dentata Zhao & Cai, A. dilatata Cai & Tomokuni, and A. papilla Zhao & Cai are described as new species. A key to the world species of the genus is also provided. The diagnostic characters both for the genus and the species group are modified.